2022
DOI: 10.3389/fonc.2022.1057455
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin, characterized as a HDAC6 inhibitor, inhibits gastric cancer metastasis

Abstract: Gastric cancer is a common gastrointestinal cancer. Survival outcome for patients with the recurrence or metastasis remains poor due to the lack of effective targeting drugs. The mechanisms of non-histone acetylation modifications are key epigenetic regulations that participate in various biological processes. HDAC6 is mostly located in the cytoplasm to deacetylate non-histone substrates, which has been identified as a critical promoter of many oncogenic pathways in cancers, including gastric cancer. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…7). Recently, another study suggested that canagliflozin directly targets and suppresses HDAC6 in gastrointestinal cancer cells [60], indicating that HDAC targeting may be a common pathway for the activity of this drug in tumors. Many of the genes that were significantly upregulated by RT (FGFR1, ALDOA, RNF145, PGK1, P4HA1, PLOD2, IGFBP3, NDRG1, PFKFB3, and BNIP3L) are associated with glycolysis, cell cycle progression, prevention of apoptosis, angiogenesis, cholesterol homeostasis, and survival, which contribute to resistance to cytotoxic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Recently, another study suggested that canagliflozin directly targets and suppresses HDAC6 in gastrointestinal cancer cells [60], indicating that HDAC targeting may be a common pathway for the activity of this drug in tumors. Many of the genes that were significantly upregulated by RT (FGFR1, ALDOA, RNF145, PGK1, P4HA1, PLOD2, IGFBP3, NDRG1, PFKFB3, and BNIP3L) are associated with glycolysis, cell cycle progression, prevention of apoptosis, angiogenesis, cholesterol homeostasis, and survival, which contribute to resistance to cytotoxic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Recently, another study suggested that canagliflozin directly targets and suppresses HDAC6 in gastrointestinal cancer cells [ 60 ], indicating that HDAC targeting may be a common pathway for the activity of this drug in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on drug regulation of autophagy and epigenetics offer new treatment targets for ID. Canagliflozin, a sodium-glucose cotransporter-2 inhibitor approved by the Food and Drug Administration for the treatment of diabetes, targeted the epigenetic modifiers histone deacetylases 6 and 2, inhibiting the progression of tumors ( 6 , 7 ) and activated autophagy yielding anti-inflammatory effects ( 8 ). Canagliflozin attenuated renal fibrosis in vitro and in vivo through an autophagy-mediated m 6 A modification ( Yang et al.…”
mentioning
confidence: 99%